A bibliometric analysis of customer engagement research in the hospitality and tourism industry / Purva Kansal and Shipra - Kansal, Purva; Shipra (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2023)
Over the past few years, customer engagement (CE) has emerged as an important concept in the marketing discipline. Despite the voluminous literature on the area in the hospitality and tourism (H&T) industry, there is a lack of studies that provide a structure to the existing literature, and as a result, the directions to advance this research area are not clear. To address this gap, the present study aimed to present a state-of-the-art review of CE research in the H&T industry and highlight potential areas for future research. In order to achieve this objective, a bibliometric analysis of 211 articles published in 85 Scopus-indexed journals between 2009 and 2023 was done. The results indicated that the number of publications on CE in the H&T industry has increased, especially after 2019, and is clustered around four themes: consequences of CE, CE in the digital age, CE as a tool to build customer relationships, and tourists CE with the destination. The results further revealed the most productive and influential journals, articles, authors, and countries in the area of CE in the H&T industry. By highlighting the current status of the field and the potential areas for future research, the study is believed to assist academicians and researchers in taking this research area forward.